The Present Past in Croatia: Perception of War Victims and War Crimes among Serbs and Croats - Kardov, Kruno; Teršelič, Vesna (2007)
The authors will discuss survey research results on coming to terms with the past in Croatia. The research was conducted in 2006 on a representative sample of Croatia's majority population (N=700), and two additional samples of Serbs (N=150) and Croats (N=150) from war-torn regions. The authors will give stress on two sets of questions: attitudes towards war victims and perception of different categories of victims (e.g. Serbian and Croatian victims, military and civil victims, etc.) and attitudes towards war crimes and responsibility. The results show that the perception of different categories of victims varies between Serbs and Croats. The same results also suggest that the moral judgements on innocence play important role in public's perception of the victims. Data related to questions of war crimes show that the majority of respondents are ready to acknowledge the existence of war crimes committed by the members of their own ethnic group, although such war crimes are evaluated differently in comparison to the crimes committed by members of the other ethnic group. In general the crimes committed by members of the other ethnic group are seen as planned, aimed against whole ethnic group, based on hate and are seen as crimes that cannot be justified. On the other hand, regardless of the nationality of the respondents, crimes committed by the members of one's own ethnic group are tended to be seen as individual, as crimes committed from necessity, aimed against particular individuals and which could even be justified. Furthermore, the results show that the respondents tend to attribute responsibility for other group's war crimes to a greater number of social groups as well as to the military commanders and, for war crimes committed by the members of their own ethnic group, to individual perpetrators only and to smaller number of social groups.
Projekt MZOS
ENG